CRISPR/Cas9 gene editing in Drosophila melanogaster - Kaltenböck, Konstantin (Jihočeská univerzita, 2021)
The aim of this thesis was to predict functional sites in the timeless gene of Drosophila melanogaster, to design fitting gRNAs for the identified sites to create transformation vectors for fly transformations and to induce CRISPR/Cas9 mediated target mutations by crossing gRNA expressing flies with Cas9 expressing flies.
CRISPR/Cas9 gene editing in Drosophila melanogaster
Keywords: Gene editing; CRISPR/Cas9; Drosophila melanogaster; circadian clock; timeless; Gene editing; CRISPR/Cas9; Drosophila melanogaster; circadian clock; timeless